Applying content based instruction to develop speaking skills for students majoring in tourism at a public university in Hanoi = Áp dụng phương pháp dạy học tích hợp với nội dung để phát triển kỹ năng nói cho sinh viên chuyên ngành du lịch tại một trường đại học ở Hà Nội - Nguyễn, Tá Nam (2020)
This research aimed to find out how Content-based instruction was implemented to improve speaking skills for university tourism students and their attitudes toward this CBI method. Data were obtained through the questionnaires and teaching diaries instruments and then analyzed quantitatively and qualitatively. The findings indicate that most of the students achieved considerable progress in their speaking while being taught with CBI method in speaking lessons, and their attitudes toward CBI implementation were positive. Besides, the findings and discussion of the research suggested how to implement CBI, Theme-based Model with the approach of Stoller and Grabe forward the "six Ts" method. "Six Ts" represent themes, texts, topics, threads, tasks, and transitions into teaching students to speak in class and how to ensure that each lesson focus on both Content learning objectives and Language learning objectives.